ANALISIS KINERJA PLTS ON GRID 3.540 WP DENGAN BEBAN MESIN PENCACAH SAMPAH 2HP DI FAKULTAS TEKNIK UKI JAKARTA - Pabika, Obet; Susilo, Susilo; Widodo, Bambang (Prodi Teknik Elektro FT UKI, 2024)
ABSTRACT Fossil energy, which is the main source of electricity generation in many countries, makes a major contribution to air pollution and greenhouse gas emissions. Volioh photo solar energy panels (PV) offer an environmentally friendly solution, by utilizing abundant and unlimited solar energy. On-grid PV systems connect solar power plants to the power grid, enabling distributed energy production and efficient utilization of renewable resources. This research The use of on-grid PV-based solar energy is expected to be an important step in creating a more sustainable, efficient and environmentally friendly energy system. The results of the research show that when measuring PV without load, the PV voltage increases as the light intensity received by the PV increases, but the PV voltage experiences saturation starting from the light intensity of 164 lux. In the PV test under load the voltage is almost constant around (226.2 to 237.6) votl with changes in load current around (4.94 to 6.76) A Keywords: Solar Power Plant (PLTS). On-grid, Renewable Energy, Photovoltaic (PV) Solar Panels.